Korea's preference for redistribution and the policy decisions - Soo Kyeong Hwang (Korea Development Institute (KDI), 2020)
While Korea's compressed development has enriched and bolstered the economy, the social system still leaves much to be desired. The reason for this shortcoming lies within a short history of capitalism and growth-oriented policies that sacrifice distribution. The end of Korea's accelerated growth and ensuing sharp drop in social mobility-which drove the dynamics of Korean society-have incited growing concern over income inequality and inherited wealth. As a result, more and more people have begun to recognize the need for redistribution policies to resolve the socioeconomic inequality. The problem is, however, how much redistribution policy will meet the people's expectations? As evidenced by the controversies over the policies for free school meals and half-price tuition from 2010, and by the response to the various redistribution policies of the Moon Jae-in administration, Koreans are highly divided in their opinions about the level of redistribution. Nonetheless, little effort has been made to understand the degree to which views differ, and to discover the factors that lead to such conflict. Rather, debates over policy are overly focused on theoretical justification, which has served to escalate social tension, and there have been no substantial moves towards building social consensus on distributive justice. The policies of a democracy are not justified by abstract goals and political rhetoric, but through the people's support. Thus, a good grasp is first needed of the wide array of public opinion. This study aims to highlight this issue. [...]
Keywords: 330; Umverteilung; Öffentliche Meinung; Politische Entscheidung; Gruppenentscheidung; Südkorea